Blazar monitoring with LOFAR. Issue Volume 10:Issue S313(2014) (24th March 2015) - Turriziani, Sara; Hardcastle, Martin; Miller-Jones, James; Broderick, Jess; Markoff, Sera; ,
Abstract: We have been monitoring some well-known bright blazars with short LOFAR observations since February 2013 with fortnightly cadence using the full available bandwidth of the High Band Antennas (i.e., 48 MHz centred at 226 MHz). The sources were chosen to be bright at low frequencies and to exhibit strong GHz-frequency radio variability on timescales of weeks to years. None of the five objects selected have been monitored previously in the MHz band. Here we report some preliminary results on flux variability obtained so far with LOFAR. These observations are scientifically valuable in their own right and also act as a proof of principle for broader, higher-cadence monitoring of the extragalactic sky with LOFAR and possibly SKA.